The Circumnuclear Environment of IRAS 20551-4250: A Case Study of AGN/Starburst Connection for JWST - E. Sani; E. Nardini (Advances in Astronomy)
We present a general review of the current knowledge of IRAS 20551-4250 and its circumnuclear environment. This Ultraluminous Infrared Galaxy is one of the most puzzling sources of its class in the nearby Universe: the near-IR spectrum is typical of a galaxy experiencing a very intense starburst, but a highly obscured active nucleus is identified beyond ~5 μm and possibly dominates the mid-IR energy output of the system. At longer wavelengths star formation is again the main driver of the global spectral shape and features. We interpret all the available IR diagnostics in the framework of simultaneous black hole growth and star formation and discuss the key properties that make this source an ideal laboratory for the forthcoming James Webb Space Telescope.